Study Of Tuban Regency Regional Budget Independence In Regional Economic Development 2019-2023 - Parikesit Penangsang; Pramita Studiviany; Adiati Trihastuti (Jurnal Multidisiplin Sahombu, 2024)
This study aims to analyze the Independence of the Tuban Regency Regional Budget through the analysis of the regional financial independence ratio. The data used are secondary data in the form of regional financial reports obtained from the Regional Financial and Asset Management Agency during the period 2019 to 2023. The analysis method applied is quantitative descriptive. The results of this study indicate that the independence ratio of Tuban Regency is still low, reflecting a consultative relationship pattern, namely dependence on transfer funds from the government. The description of the condition of regional financial independence of the Tuban Regency government from 2019-2023 averaged 28.10% with a consultative relationship pattern, and low regional financial capacity of 28.10%. Government intervention of 71.90%, decreased because the regional government was considered to be starting to be able to implement regional autonomy. However, in 2023 regional financial independence decreased, namely at a value of 25.51% because PAD in that year was lower than the previous year.